2019
DOI: 10.1093/femsre/fuz017
|View full text |Cite
|
Sign up to set email alerts
|

Do phenothiazines possess antimicrobial and efflux inhibitory properties?

Abstract: Antibiotic resistance is a global health concern; the rise of drug-resistant bacterial infections is compromising the medical advances that resulted from the introduction of antibiotics at the beginning of the 20th century. Considering that the presence of mutations within individuals in a bacterial population may allow a subsection to survive and propagate in response to selective pressure, as long as antibiotics are used in the treatment of bacterial infections, development of resistance is an inevitable evo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 111 publications
(115 reference statements)
1
39
0
Order By: Relevance
“…As previously stated, Ca 2+ plays a pivotal role in many metabolic pathways including transport systems and are essential for signaling. The antimicrobial properties of the phenothiazines have been described since 1930 and 1940 (Grimsey and Piddock, 2019). The ways by which phenothiazines exert their antimicrobial effect include, damaging cell membranes, inhibiting Ca 2+ -dependent processes, disrupting cationdependent transporters, acting as antagonist of Ca 2+ -binding proteins and in other ways (Grimsey and Piddock, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously stated, Ca 2+ plays a pivotal role in many metabolic pathways including transport systems and are essential for signaling. The antimicrobial properties of the phenothiazines have been described since 1930 and 1940 (Grimsey and Piddock, 2019). The ways by which phenothiazines exert their antimicrobial effect include, damaging cell membranes, inhibiting Ca 2+ -dependent processes, disrupting cationdependent transporters, acting as antagonist of Ca 2+ -binding proteins and in other ways (Grimsey and Piddock, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The antimicrobial properties of the phenothiazines have been described since 1930 and 1940 (Grimsey and Piddock, 2019). The ways by which phenothiazines exert their antimicrobial effect include, damaging cell membranes, inhibiting Ca 2+ -dependent processes, disrupting cationdependent transporters, acting as antagonist of Ca 2+ -binding proteins and in other ways (Grimsey and Piddock, 2019). Therefore, we investigated the effect of Ca 2+ on the efflux of EtBr first by analyzing the effect of various divalent metals (Supplementary Material).…”
Section: Discussionmentioning
confidence: 99%
“…S2b); however, this concentration did not reduce pKpQIL transconjugants. The concentration range that we tested goes above the peak serum concentrations of chlorpromazine (0.1 g/ml) (63). We aimed to test concentrations of compounds that were within the therapeutic window.…”
Section: Plasmid Transmission Is Impacted By the Ratio Of Donor And Rmentioning
confidence: 99%
“…Studies in the past decades on phenothiazines, primarily used as antipsychotic drugs, but also known for their multifunctionality, have disclosed that not only do they enhancein particular conditions-the effect of antibiotics, but may also have inherent antibacterial properties and therefore may be of help in combating MDR [77]. It has been indicated that phenothiazine derivatives, including fluphenazine, thioridazine (TZ), perphenazine and chlorpromazine (CPZ), can interfere with DNA replication [78,79], may influence cellular energy generation [80,81] and inhibit biofilm production [82,83].…”
Section: Terrestrial Microbial Concerns: Approaches For Multiple Drug Resistancementioning
confidence: 99%